Direct Oral Anticoagulants vs. Vitamin K Antagonists in Atrial Fibrillation Patients at Risk of Falling: A Meta-Analysis - Gao, Xinxing; Huang, Donghua; Hu, Yuting; Chen, Yuanyuan; Zhang, Haidong; Liu, Fuwei; Luo, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background Direct oral anticoagulants (DOACs) and warfarin are usually used for people with atrial fibrillation (AF). However, for the AF patients at risk of falling, the effectiveness and safety outcomes of DOACs compared with warfarin remain unclear. Therefore, we performed a meta-analysis regarding the effectiveness and safety of DOACs vs. warfarin in AF patients at risk of falling. Methods A search of the PubMed and Embase databases until November 2021 was performed. We included studies if they satisfied the following criteria: (1) study type: randomized clinical trials or observational cohort studies. (2) Comparisons: effectiveness and/or safety of DOACs (dabigatran, rivaroxaban, apixaban, or edoxaban) compared with warfarin. (3) Study data: the sample size, the number of events in the VKAs or DOACs groups, adjusted risk ratios (RRs), and 95% confidence intervals (CIs). (4) Study outcomes: stroke or systemic embolism (SSE), ischemic stroke, myocardial infarction (MI), all-cause death, and cardiovascular death; major bleeding, major or clinically relevant non-major (CRNM) bleeding, intracranial bleeding, gastrointestinal bleeding, and any bleeding. (5) Study population: patients at risk of falling. According to the Morse Fall Scale, the risk of falling relates to the history of falling, secondary diagnosis, ambulatory aids, intravenous therapy, type of gait, and mental status. In this meta-analysis, if the patient's MFS score is ≥25 points, he will be thought of as having the risk of falling. The adjusted risk ratios (RRs) and 95% confidence intervals (CIs) were pooled by a random-effects model with an inverse variance method. Results Three cohort studies were included in our study. For the effectiveness outcomes, the use of DOACs was only associated with a significantly reduced risk of hemorrhagic stroke (RR = 0.28, 95%CI:0.10–0.75) compared with warfarin, but there were no significant differences in stroke or systemic embolism (SSE) (RR = 0.87, 95%CI:0.70–1.08), cardiovascular death (RR = 0.97, 95%CI:0.73–1.29) and all-cause death (RR = 0.90, 95%CI:0.72–1.11). For the safety outcomes, the use of DOACs was significantly associated with reduced risks of major or clinically relevant non-major bleeding (RR = 0.77, 95%CI:0.61–0.98) and intracranial bleeding (RR = 0.26, 95%CI:0.11–0.66) but not major bleeding (RR = 0.78, 95%CI:0.58–1.06). Conclusions Compared with warfarin, the use of DOACs in AF patients at risk of falling is significantly associated with reduced risks of hemorrhagic stroke, major or clinically relevant non-major bleeding, and intracranial bleeding.